Original paperComparison of short-term outcomes after carotid artery stenting according to different stent designs - Sahin, Muslum; Açar, Göksel; Özkan, Birol; AlıcIı, Gökhan; Yazicioglu, Mehmet Vefik; Bulut, Mustafa; Kalkan, Mehmet Emin; Demir, Serdar; Acar, Rezzan Deniz; Boztosun, Bilal (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : In the developed countries, stroke is the third most common cause of death. There are many data indicating that stents reduce the risk of embolism but there are few publications assessing whether different stent designs can influence the periprocedural complications. Aim : To determine the effects of open- and closed-cell stent designs on 1-month results of carotid artery stenting (CAS). Material and methods: The study group consisted of 290 consecutive patients (216 men and 74 women, mean age 66.6 ±8.7 years). Neuroprotection with a distal protection device was used in all cases. The patients were divided into two groups: the open-cell stent group (n = 144) and the closed-cell stent group (n = 138). Major adverse cardiac and cerebrovascular events (MACCE) described as myocardial infarction, stroke and death within 1 month were recorded and analysed subsequently. Periprocedural hypotension and transient cerebral ischaemia at 1 month after the CAS procedure were also assessed. Results : We treated 290 carotid stenoses and stents were implanted in all patients. Fifteen patients (5.5%) were treated by staged CAS due to bilateral carotid artery disease. The technical success rate was 97.2%. There was no difference in the MACCE and transient cerebral ischaemia rate at 1 month between the two groups (p = 0.44 and p = 0.94, respectively). The incidence of ischaemic stroke was lower in the closed-cell stent group (2.77% vs. 0%; p = 0.04). The periprocedural rate of hypotension was higher in the closed-cell stent group (2.1% vs. 7.2%; p = 0.04). Conclusions : Closed-cell stents are associated with a low rate of ischaemic stroke. We think that closed-cell stents may be preferred in patients at high risk of embolism.